Pengaruh Tingkat Stres Akademik pada Hasil Belajar Siswa Kelas VI SD 3 Bacin - Puryati, Lila Kurnia; Tiara Indria Sari; Dinda Permatasari; Adeena Iluh Maharani; Fitriyah Amaliyah (Universitas Palangka Raya, 2023)
The purpose of this study wass to determine whether or not effect of academic stress levels on the learning outcomes of VI grade of SD 3 Bacin students. The subjects of this study consisted of 27 students of VI grade SD 3 Bacin. The method used inthis study is quantitative. Data collection techniques using questionnaires, observation, and documentation. Then the data obtained will be analized using a simple linear regression tes with the help of SPSS version 21 program. The results of data analysis show that the calculated f value = 7.552 and the sig. 0.011. If the sig. < 0.05, then H0 is rejected and H1 is accepted. Conversely, if the sig. > 0.05, then H0 is accepted and H1 is rejected. Based on the result of the hypothesis that has been formulated, it can be concluded that there is significant effects between the level of academic stress on the mathematics learning outcome variables for VI grade SD 3 Bacin because the value is 0.011 < 0.05.